Assessment of International Training Program on ICT Applications in Agricultural Extension Management for Officials from Africa and Asia - M. Ohlan; M. Shirur; B.M. Dharmaraj (Journal of Agricultural Extension Management, 2021)
The application of Information and Communication Technologies (ICTs) has become increasingly important in agriculture. Today we are seeing the growing use of ICT in the learning process. Currently, ICT based advisory services are a part of the extension system in several developing countries. A study was conducted to assess an International training program on ICT applications in Agricultural Extension Management (Farmers' Call Centre) organized by MANAGE, under Feed the Future India Triangular Training (FTF ITT) initiative, for officials from Africa and Asia. Participants from six countries attended the training and were the respondents of the study. The Program was assessed on five points and most of the participants rated the program as excellent to good and their responses revealed that they were satisfied with the training programme